META-ANALYSIS: EFFECTIVE TOPICAL PROPOLIS FOR WOUND HEALING IN DIABETIC FOOT ULCERS - Nuh Huda; Imroatul Farida; Ceria Nurhayati (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2024)
Introduction: Diabetes Mellitus is a chronic disease that has a high prevalence globally and often causes serious complications such as diabetic foot ulcers. Diabetic foot ulcers are one of the leading causes of nontraumatic amputations and significantly affect the quality of life and health of diabetic patients. Treatment of diabetic foot ulcers is a challenge for healthcare because it involves various factors that hinder the healing process. The purpose of this study was to evaluate the effect of topical propolis as an adjuvant in the treatment of diabetic foot ulcers.Methods: Data were analyzed from quality studies indexed in the SCOPUS Quartil 1 database. Data visualization is done using Forest plots.Results: The results of the analysis showed that topical propolis made a significant contribution to the healing process of diabetic foot ulcers. Topical administration of propolis increases connective tissue deposits. It promotes better tissue regeneration, as well as reducing oxidative stress, which is a major contributor to the pathogenesis of diabetic foot ulcers. Conclusion: Topical propolis offers a new and promising approach to the treatment of diabetic foot ulcers. With its anti-inflammatory, antibacterial, and antioxidant properties, propolis can speed up the wound healing process, improve patients' quality of life, and reduce the economic burden associated with diabetic foot ulcer treatment. Although more research is needed to understand the mechanism of action of propolis thoroughly, these results lend support to the potential of propolis as an effective adjuvant therapy in the management of this chronic disease.